2018
DOI: 10.1634/theoncologist.2018-0535
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Use for Nonmetastatic Breast Cancer at Five Public South African Hospitals and Impact on Time to Initial Cancer Therapy

Abstract: In sub‐Saharan Africa, clinical decisions can be affected by resource constraints. This article analyzes the clinical and sociodemographic factors associated with receiving neoadjuvant chemotherapy among patients from a previously existing cohort: women enrolled in the prospective South African Breast Cancer and HIV Outcomes study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…114 The electronic literature search conducted to inform this section of the neoadjuvant therapy guideline identified 14 articles (from a total of 101 abstracts) on the topic of health disparities. 88,[115][116][117][118][119][120][121][122][123][124][125][126][127] The available studies evaluated associations between a range of clinical and sociodemographic factors and the use and outcomes of neoadjuvant therapy for breast cancer. Killelea et al, 122 for example, examined racial differences in the frequency and outcomes of neoadjuvant chemotherapy use and reported that neoadjuvant chemotherapy was given more frequently to African American, Hispanic, and Asian women than to White women (P 5 .001).…”
Section: Health Disparitiesmentioning
confidence: 99%
“…114 The electronic literature search conducted to inform this section of the neoadjuvant therapy guideline identified 14 articles (from a total of 101 abstracts) on the topic of health disparities. 88,[115][116][117][118][119][120][121][122][123][124][125][126][127] The available studies evaluated associations between a range of clinical and sociodemographic factors and the use and outcomes of neoadjuvant therapy for breast cancer. Killelea et al, 122 for example, examined racial differences in the frequency and outcomes of neoadjuvant chemotherapy use and reported that neoadjuvant chemotherapy was given more frequently to African American, Hispanic, and Asian women than to White women (P 5 .001).…”
Section: Health Disparitiesmentioning
confidence: 99%
“…Furthermore, we enriched our cohort with patients with stage III/IV tumours by using cell blocks, making our sample more representative of the 'real' breast cancer population. Moreover, unlike retrospective series with high losses to follow-up (up to 48%), [15][16][17][18][19] only 9% of our patients were considered lost.…”
Section: Discussionmentioning
confidence: 80%
“…Our cohort study has many advantages compared with other African reports. [15][16][17][18][19] We used ISH to assess HER2equivocal cases and evaluated Ki67, and as such were able to categorise surrogate intrinsic subtypes according to the St. Gallen classification, which is often used to Values in bold are considered to be statistically significant. *p value for the univariate survival analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delays in receiving neoadjuvant or adjuvant chemotherapy involve an interplay of sociocultural elements and resource constraints even within a single SSA country. 36 Improving access through regulatory mechanisms, improved quality of imports, compulsory licensing, and implementation of universal health care would likely improve outcomes. 37 …”
Section: Discussionmentioning
confidence: 99%